Awareness and Perceptions of Artificial Intelligence among Librarians in University Libraries in Kwara State, Nigeria - Eiriemiokhale, Kennedy Arebamen; Sulyman, Abdulakeem Sodeeq (Department Library of Governance Institut of Home Affairs, 2023)
Abstract Problem Statement: The invention of Artificial Intelligence (AI) has greatly enhanced the potential of academic libraries' services. Purpose: This study explores the awareness and perceptions of AI among librarians in university libraries in Kwara State, Nigeria. Method: It adopted descriptive survey method. The population of this study are 37 professional librarians in University of Ilorin’s and Kwara State University’s libraries. Census enumeration sampling technique was used to select the respondents. Questionnaire was used to collect data from the respondents, with the support of two research assistants. Data collected was analysed and presented in frequency, simple percentages and mean (x). Result: Findings revealed that chatbots and Dynamed are the AI the respondents were aware of. The respondents have the perceptions that AI technologies can be adopted in university libraries, capable of replacing human librarians in future and AI is a positive development for librarians. Findings further indicated that the respondents perceived that AI is beneficial in university libraries because it provides patron-tailored recommendations to items, can reduce manual and repetitive tasks performed by librarians and facilitates the discovery of new knowledge. But the major factors affecting the adoption of AI include poor internet connectivity and lack of expertise among librarians. Conclusion: This study concluded that librarians’ awareness of AI influences their perceptions of it. It recommends among others that management of university libraries in Kwara State should train their librarians on AI. Keywords: Awareness, Artificial intelligence, Kwara State, Librarians, Perceptions, University libraries,